Teenage pregnancy: the influence of family and social background in the city of Anápolis – GO (Research, Society and Development, 2021)
Introduction: Teenage pregnancy (GA) is an important public health issue, due to its high prevalence and implications for pregnant women and newborns. Objectives: Describe the social data and family history that act as predisposing factors for GA in adolescent puerperal women whom attended at a public hospital in the city of Anápolis, Goiás, Brazil. Methodology: Cross-sectional, epidemiological study and quantitative approach. A questionnaire was applied to puerperal adolescents aged 10 to 19 years hospitalized after childbirth. Results: There was a predominance of GA history of the mother of the puerperal teen, demonstrating the influence of the parents in the decision making of their children. The presence of support and good family routine were prevalent, contradicting the existing literature. A large number of unplanned pregnancies was noted, indicating low knowledge for pregnancy prevention. As for social aspects, the minority had experienced family violence, also contrary to the existing literature that shows higher numbers. In general, girls had sex education at school, which demonstrates low effectiveness of classes in modifying behaviors. A high number of interviewees had access to a nearby primary health unit, which demonstrates a failure in the orientation of adolescents regarding their sexual life. Finally, adolescents, in general, did not use illicit or illicit drugs. Conclusion: The present study shows that a violent and unhealthy environment is not mandatory for the occurrence of GA, but family members have great influence on the adolescent's behavior, with better articulation of health education in schools and primary health units being important.